Activity-based pricing in small and medium-sized restaurants. Evidence from the Italian context. Issue 4 (19th August 2020) - Raucci, Domenico; Lepore, Dominique; Sabatiello, Rossella
Abstract : Purpose: This paper aims to present an extension of price sensitive measurement (PSM) combined with activity-based costing (ABC) for supporting activity-based pricing approaches in the small and medium-sized restaurants. Design/methodology/approach: The joint model of PSM and ABC is applied to the fixed menu pricing analysis of a typical medium-small Italian restaurant. Findings: The outcomes confirm the potential of the activity-based pricing approach for supporting pricing decision-making in the small and medium-sized restaurants. However, the complexity of the model for these contexts suggests testing simplified versions of ABC, proposed for other sectors, to exploit integration with PSM. Further, the authors find evidence of the need to further investigate the role of informal conditions, characterizing small-medium enterprises, which may play for the successful implementation of the approach proposed. Originality/value: There is no analysis using the suggested approach for supporting menu pricing in medium-small restaurants. This case study contributes to the literature on activity-based pricing for small and medium-sized restaurants, based on the ABC approaches.